2016
DOI: 10.1016/j.ajodo.2016.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of chewing gum and ibuprofen in the management of orthodontic pain with fixed appliances: A pragmatic multicenter randomized controlled trial

Abstract: This cover sheet may not be removed from the document.Please scroll down to view the document. Methods: Patients about to undergo orthodontic treatment using upper and lower fixed appliances were recruited into this 2-arm parallel design RCT in 9 trial sites in the South West of England. They were randomly allocated to one of two groups, namely the experimental chewing gum group or control ibuprofen group. Eligibility criteria included patients undergoing upper and lower fixed appliance therapy, aged 11-17 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 19 publications
2
39
1
6
Order By: Relevance
“…The methodology and results of this trial have been reported elsewhere (Ireland et al 2016). At the same time patients were asked to record their levels of anxiety using a Likert scale immediately following the fitting of the appliance and the first archwire change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology and results of this trial have been reported elsewhere (Ireland et al 2016). At the same time patients were asked to record their levels of anxiety using a Likert scale immediately following the fitting of the appliance and the first archwire change.…”
Section: Methodsmentioning
confidence: 99%
“…As with the initial pain and chewing gum/ibuprofen use analysis, the data were analyzed using STATA version 14 (STATA Corp, USA) and the analytical approaches reported for the main trial results (Ireland et al 2016) were used here, but in this case including anxiety score in the models as a putative predictor. Specifically, multi-level models were fitted with treatment group, time point (and the interaction between treatment group and time point, since this was statistically significant) and anxiety as fixed effects, centre as a random effect and individual (nested within centre) also as a random effect; random effects in both cases were included as intercept terms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Son action cario-protectrice est principalement liée aux effets sur la phase minérale de l'émail, sur le processus de reminéralisation [4,7,12,14], et son effet sur la prolifération bactérienne [14,19]. Les chewinggums, de par leurs effets sur la stimulation des muscles masticatoires, diminuent significativement la douleur lors de la pose ou de la réactivation du dispositif [3,9]. Une diminution de la prise d'analgésiques a été mise en évidence chez des patients ayant recours aux chewing-gums sans sucre après la pose ou la réactivation d'un dispositif [9,15].…”
Section: Introductionunclassified
“…Les chewinggums, de par leurs effets sur la stimulation des muscles masticatoires, diminuent significativement la douleur lors de la pose ou de la réactivation du dispositif [3,9]. Une diminution de la prise d'analgésiques a été mise en évidence chez des patients ayant recours aux chewing-gums sans sucre après la pose ou la réactivation d'un dispositif [9,15]. Cependant, leur consommation durant un traitement orthodontique doit rester occasionnelle d'une part, car le brossage mécanique avec une brosse à dents et du dentifrice est le moyen le plus efficace d'assurer une bonne hygiène bucco-dentaire, mais également car ces chewing-gums sans sucre ont tendance à être assimilés par les jeunes patients ou leurs parents à des sucreries à potentiel cariogène comme les bonbons ou aux chewing-gums contenant du sucre.…”
Section: Introductionunclassified